The Influence of Employee Skills, Coordination, and Job Description on Employee Performance: The Mediating Role of Managerial Control in the National Land Agency in Buleleng Regency - Widya Halmahe Rani; Ni Luh Eka Ayu Permoni (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze the influence of employee ability,coordination, and job description on employee performance, with controlling as a mediating variable, at the Buleleng Regency National Land Agency (BPN) Office. The research uses a quantitative approach with purposive sampling involving 66 employees who meet predetermined criteria. Data were collected through strutured questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results show that job description has a significant effect on controlling, and controlling has a significant effect on employee performance. Employee ability also has a proven direct effect on performance. However, employee ability and coordination do not have a significant effect on controlling or on performance through controlling. Likewise, coordination and job description do not have a direct effect on employee performance. These findings emphasize the crucial role of managerial controlling in linking job description clarity with employee performance outcomes. Therefore, strengthening the control system and ensuring that job descriptions are well-defined and effectively communicated are key strategies for improving performance in public sector organizations, particularly in the land administration domain.